Scoping Review on Ethical Considerations in Research on the Work–Family Interaction Process - Miguel Valencia-Contrera; Flérida Rivera-Rojas; Jenifer Villa-Velásquez; Daniella Cancino-Jiménez; Solange Vallejos-Vergara; Naldy Febré (Nursing Reports)
Background: The complex nature of the work–family interaction process means special ethical considerations are required in its study. Symphonology can guide ethical analysis in this area, as it pertains to the study of agreements and the elements necessary to form them. Objective: Our objective was to analyze the ethical considerations involved in the development of research on the work–family interaction process via symphonological bioethical theory. Methods: A scoping review was conducted by consulting the following databases: Web of Science (WoS), SCOPUS, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PubMed, and Business Source Ultimate. Given the small number of studies identified in the field, we did not discriminate by years of publication and included articles of any design that addressed ethical considerations in research on the work–family interaction process or that were related to the topic, including manuscripts in Spanish, English, and Portuguese. Results: The ethical analysis of research on the work–family interaction process requires us to consider the participant’s multi-role status as a “worker,” including their inherent relationships with their environment, such as colleagues and supervisors, and as a member of a “family” unit. The various factors involved in the work–family interaction “context” must be analyzed within the context of situation, knowledge, and awareness. Based on the review findings, a list of recommendations was developed focused on planning, data collection, and result presentation. Key points include the provision of psychological support when the research involves sensitive data; the notification of authorities upon identifying offenses such as workplace abuse or domestic violence; and ensuring confidentiality of participation. Conclusions: This review provided answers to the proposed objective, concluding that the symphonological nursing bioethics theory, through its conception and statements, guides researchers to make decisions in the context of research development in the work–family interaction process.